Unmet Need for Contraception Among Female Sex Workers Initiating Oral Pre-Exposure Prophylaxis for HIV Prevention During Kenya's National Scale-Up: Results From a Programmatic Surveillance Study - Kamau, Mercy; Musau, Abednego; Were, Daniel; Waruguru, Gladys; Kabue, Mark; Mutegi, Jane; Plotkin, Marya; Reed, Jason (Frontiers in Global Women's Health, 2022)
Female sex workers (FSW) experience a higher risk for HIV acquisition and unwanted pregnancies compared to women in the general population. Pre-exposure prophylaxis (PrEP) for HIV prevention offers promise for FSW who inconsistently use condoms but has no protective effect on unintended pregnancies. Understanding the magnitude and determinants of unmet need for contraception among FSW, who initiated PrEP in a large-scale PrEP service delivery program, could inform program re-design to optimize contraceptive delivery and avert unwanted pregnancies. We conducted a study to examine the determinants of unmet need for contraception among FSW initiating PrEP in Kenya. This study employed a cross-sectional analysis on de-identified client data from the Jilinde project. Data were collected routinely during clinic visits using Ministry of Health approved tools. Eligible records for all FSW initiated on PrEP from 79 health facilities between February 2017 to December 2019 were analyzed. Unmet need for contraception among reproductive age FSW was defined as not being pregnant, not using contraception, and not intending to have a child in the near future. Univariate and multi-variable regression analysis were conducted with selected variables to examine associations. In the 79 sites, 17,063 FSW initiated PrEP. Two-thirds were under 30 years and the majority were not married and received PrEP through drop-in centers. Unmet need for contraception was 52.6% with higher percentages for younger FSW and those served in public and private health facilities. FSW from the Nairobi and Coast cluster regions reported higher unmet need for contraception compared to those from the Lake region. All these associations were significant (p<0.05) at the multi-variate level. The high unmet need for contraception among FSW at their PrEP initiation visit highlights the need for integrated delivery of contraception services within PrEP programs. Identifying groups with a higher unmet need could optimize uptake of the paired interventions. Training health care providers, delivering contraception messaging during demand creation for PrEP, and making contraceptives accessible o FSW who are initiating PrEP could mitigate the gaps identified by this study and synergize prevention.